The role of media in exposing violation of child’s rights and gender abuse by Boko Haram terrorists in Nigeria - Mohammed Ibrahim, Adamkolo; Umar Sanda, Hajara; Kolo Lawan, Aisha (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper employs journalism analytical approaches to highlight issues related to child and gender abuse perpetrated by Boko Haram terrorists in north-east of Nigeria with the aim of setting an agenda for the adoption of systematic (in addition to the traditional) developmental approaches toward enhancing children and women protection and ending the 10-year-old insurgency which has so far claimed more than 30,000 lives, forced more than 1.7 million people out of their homes and destroyed properties worth billions of Dollars that have given rise to one of the largest humanitarian crises in the world. The group’s notoriety came to limelight after a surprising abduction of nearly 300 schoolgirls in the Borno State town of Chibok, an incident that gave rise to the global #BringBackOurGirls campaign. Role of the media in the protection of children and women as well as counter-terrorism were critically discussed and policy recommendations offered.